Between Chronos and Kairos – Existential Dilemma of an Archaeologist - Mierzwiński, Andrzej (Analecta Archaeologica Ressoviensia, 2017)
Archaeology wants to estimate the moment of origin of every thing, with all the related phenomena or processes. It wants to master the methods of measuring their duration. An ordinary archaeologist feels more like a chronometrist than an expert in man in different cultural contexts. Perhaps listening to the bustle of everyday life should constitute the essence of our efforts. Normalized time, regarded as objectively given, marginalizes cognitive importance of heterogeneous time, which is a unique, axiological measure of specific reality. Chronos, an all-preceding god, is the possessor of the repeated and evenly passing (eternal) time. In our research he thus dominates socially inclined Kairos, the youngest of gods, who brings the right time to perform an action. Volatile gift of Kairos has to be grasped at the right moment and given a unique meaning, i.e. value. Thanks to the scientific contextualization of time one can freely refer to the time of Chronos.